Primary blood neutrophils express a functional cell surface Toll‐like receptor 9. Issue 8 (9th August 2013) - Lindau, Dennis; Mussard, Julie; Wagner, Britta J.; Ribon, Matthieu; Rönnefarth, Viktoria M.; Quettier, Maude; Jelcic, Ivan; Boissier, Marie‐Christophe; Rammensee, Hans‐Georg; Decker, Patrice
<x xml:space="preserve">Abstract</x> Polymorphonuclear leukocytes (PMNs) represent one of the first lines of defense against pathogens. TLR9 is normally expressed in endosomes/lysosomes where it is activated by pathogen‐derived DNA. Here we show that freshly isolated human and mouse primary PMNs express TLR9 at the cell surface ex vivo. Moreover, surface TLR9 expression is upregulated upon activation of PMNs with different stimuli and not only TLR9 agonists. Importantly, surface TLR9 is processed, active, and functional. TLR9 ligands, oligo‐nucleotides containing unmethylated CpG motifs, indeed bind to surface TLR9 and binding was strongly observed at the cell surface of human cells expressing surface TLR9 and at the surface of WT but not TLR9‐deficient mouse PMNs. Finally, CpG oligonucleotides cross‐linked onto a solid phase and having no access to intracellular TLR9 are able to trigger cell surface TLR9 and induce neutrophil activation, even when endosomal acidification is inhibited. This is the first demonstration of a functional TLR9 expressed at the cell surface of human primary cells. This pathway may be triggered when pathogen‐derived TLR9 ligands cannot reach the endosome, offering a rescue mechanism for neutrophil activation.